Multibeam antennas for 5G communication systems - Zhou, Xiaohan (Nanyang Technological University, 2022)
With the development of satellite navigation, ship communication, radar ranging and 5G wireless communication system, multibeam antennas are widely used. And the requirements for multibeam antennas are increasingly stringent. Lens antenna has a wider application prospect because of its advantages of low hardware cost, wide band and wide angle scanning range. To solve the difficulties faced by the lens antenna, the thesis carries out research on the miniaturization, planarization and easy integration of the lens antenna while maintaining the excellent focusing performance and wide angle scanning characteristics of the lens antenna. The main work of this thesis is to propose a new low profile all-metal multibeam lens antenna. Based on the theory of geodesic Luneburg lens antenna, the lens is an air-filled lens antenna with lower lens profile and simpler lens curve. The simulation results show that the lens antenna achieves the beam coverage of ±70° on the H-plane and gain of 15.4dB.